A Global Census of Metals in the Universe - Saloni Deepak; J. Christopher Howk; Nicolas Lehner; Céline Péroux (The Astrophysical Journal, 2025)
We present a census of the mass density of metals and their evolution with cosmic time on a global scale throughout the Universe, synthesizing robust estimates of metals in stars, hot intracluster gas, and gaseous absorbers tracing neutral gas as well as ionized gas in the circumgalactic and intergalactic media. We observe an order of magnitude increase in the stellar metal mass density from z  ∼ 2.5 to 0.7, over which time stars emerge as the most important metal reservoir at low redshifts, housing ∼30% of the total expected metal density at z  ∼ 0.1. Hot virialized intracluster/intragroup gas accounts for ∼15% and 10% of metals at z  ∼ 0.1 and 0.7, respectively. Using metallicity measurements from the COS CGM Compendium, KODIAQ-Z, and the HD-LLS surveys covering redshifts z  < 1 to z  ∼ 2–3.5, we investigate the global distribution of metals in extragalactic cool ionized gas as a function of H i column density. During the period from z  ≈ 3 to z  < 1, the global metal density of cool ( T  ∼ 10 ^4−5 K) gas has doubled. However, the fractional contribution of the ionized gas to the total expected metal density decreased from ∼20% at z  ∼ 3 to ∼4% at z  < 1. The cosmic metal density of all gas phases has increased with cosmic time, reflecting an “inside-out” metal dispersion by feedback mechanisms and galactic outflows.